Synthesis of Sodium Myristyl Sulfate with Myristyl Alcohol Sulfation using SO3-DMF - Sitinjak, Elvri Melliaty; Masmur, Indra; Tarigan, Dedi; Anggini, Cindy; Simbolon, Emma Juli Anamasta; Simatupang, Endang; Pane, Yulia Ratu; Simorangkir, Murniaty; Nurfajriani, Nurfajriani (Universitas Negeri Medan, 2023)
The sulfation reaction between myristyl alcohol and the SO3-DMF complex has been successfully carried out to produce sodium myristyl sulfate. Formation of the SO3-DMF complex by reacting DMF and SO3 gas obtained from the reaction of phosphorus pentaoxide and H2SO4. The variables studied were the time of formation of the complex, the time and temperature of sulfation and the concentration of NaOH at neutralization. The results of myristyl alcohol sulfation with SO3-DMF were tested by FTIR spectroscopic analysis, surface tension test, and foam stability test. The formation time of the SO3- DMF complex of 5 hours is the result of the highest surface tension reduction and the most optimal foam stability. The results of the foam stability test analysis showed the highest value at 80oC with a foam stability of 0.5 cm. The best result of sulfation neutralized with 40% NaOH solution was able to reduce the surface tension value and has foam stability up to 66% with a decrease in foam height of 0.3 cm